THE INFLUENCE OF WATCHING YOUTUBE PRONUNCIATION VIDEOS TOWARDS STUDENTS’ PRONUNCIATION ABILITY - Danu Herjuantoro; Syaifudin Latif Darmawan (Intensive Journal, 2018)
In language teaching, media is one of the tools that very useful to support its successful teaching. In teaching pronunciation, the students need to give additional information how to pronounce words. One of the ways is by using Youtube pronunciation videos. By using Youtube pronunciation videos, the students will get more input and knowledge how to pronounce words from the native. The objective of this research is to know whether there is a significant influence of watching Youtube pronunciation videos towards students’ pronunciation ability. There were two variables in this research, the independent variable (X) was Youtube Pronunciation videos and dependent variable (Y) was the students’ pronunciation ability. The research method used was experimental design. The researchers dealt with two classes, they were an experimental class and a control class. In the experimental class, the researchers used Youtube pronunciation videos, whereas in control class the researchers did not use any media. Each class received the same pre-test and post-test. The population of this research was the second year students of MAN 1 Model Bandar Lampung. The samples of this research were two classes consisting of 90 students. In collecting the data, the researchers used reading aloud test as the instrument.After doing the data analysis, it was found that there is a significant influence of using videos towards students’ pronunciation ability. It can be seen from the result of the T test that T-observed was 5.34615, and the result of T-critical was 1.67. It means that T-observed was higher than T-critical (T-observed> T-critical). Therefore, the hypothesis is accepted. This result means that there is significant influence of watching Youtube pronunciation videos towards students’ pronunciation ability.